A Novel Design of a Microstrip Microwave Power Amplifier for DCS Application using Collector-Feedback Bias - Amine Rachakh; Larbi El Abdellaoui; Jamal Zbitou; Ahmed Errkik; Abdelali Tajmouati; Mohamed Latrach (Institute of Advanced Engineering and Science, 2018)
This paper presents a 1.80GHz class-A Microwave power amplifier (PA). The proposed power amplifier is designed with single-stage architecture. This power amplifier consists of a bipolar transistor and improved by Collector-Feedback Biasing fed with a single power supply. The aim of this work is to improve the performance of this amplifier by using simple stubs with 50Ω microstrip transmissions lines. The proposed PA is investigated and optimized by utilizing Advanced Design System (ADS) software. The simulation results show that the amplifier achieves a high power gain of 13dB, output power rise up to 21dBm and good impedances matching ;For the input reflection coefficient (S11) is below than - 46.39dB. Regarding the output reflection coefficient (S22) is below than -29.898dB, with an overall size of about 93 x 59mm². By the end; we find that this power amplifier offers an excellent performance for DCS applications.